The Race for Hafiz: Scholarly and Popular Translations at the Fin de Siècle - Bubb, Alexander (My University, 2020)
The great Persian lyric poet Hafiz was first translated into English by Sir William Jones in the 1780s. In the course of the nineteenth century many further translations would appear, initially intended for the use of oriental scholars and students of the Persian language, but increasingly also for the general reading public. The paraphrasers or ‘popularizers’ who devised the latter category of translation competed with professional scholars to shape the dissemination and popular perception of Persian poetry. Owing to a variety of factors, the middle of the nineteenth century saw a marked decline in the number of new Hafiz translations, and it is not until 1891 that a complete edition of Hafiz's works finally appeared in English. This led to an unusual situation, particular to Britain, in which scholars (Edward H. Palmer, Henry Wilberforce-Clarke, Gertrude Bell), and popularizers (Richard Burton, Herman Bicknell, Justin McCarthy, Richard Le Gallienne, John Payne) all jostled to fill the vacuum created by the absence of a definitive version. Their competition created, in short order, a diversity of versions presented to consumers, which allowed Hafiz's influence to be felt in twentieth-century poetry untrammelled by the impress (as became the case with Omar Khayyam) of one dominant translator. While the refraction of Hafiz through the biases and predispositions of multiple translators has been regarded as hopelessly distorting by Julie Scott Meisami, I argue instead that it highlights lyric, in the richness and diversity characteristic of Hafiz, as the Persian poetic mode which has been more influential on English writing and yet the most difficult to categorize and integrate. Lastly, by paying heed to the popular transmission of Hafiz in English, we might better understand the reception of Persian poetry in its generic, rather than only its formal character.
PUBLISHED
Keywords: Hafiz; Persian poetry; Translation